2012
DOI: 10.1371/journal.pone.0037435
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Aquaporin Function: Potent Inhibition of Aquaglyceroporin-3 by a Gold-Based Compound

Abstract: Aquaporins (AQPs) are membrane channels that conduct water and small solutes such as glycerol and are involved in many physiological functions. Aquaporin-based modulator drugs are predicted to be of broad potential utility in the treatment of several diseases. Until today few AQP inhibitors have been described as suitable candidates for clinical development. Here we report on the potent inhibition of AQP3 channels by gold(III) complexes screened on human red blood cells (hRBC) and AQP3-transfected PC12 cells b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
145
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 116 publications
(153 citation statements)
references
References 71 publications
3
145
0
Order By: Relevance
“…Dose-response curves are shown in Figure 2 and the IC 50 values obtained from data fits are summarized in Table 1. Inhibition of glycerol permeability in hRBC by the same metal complexes [13,14] is also reported for comparison purposes. As shown in Figure 2, the cellular behavior under the influence of the phenanthroline compounds (Auphen and Cuphen) differs significantly from the bipyridine cores (p <0.001).…”
Section: Antiproliferative Effects Of Metal Compounds In Cancer Cellsmentioning
confidence: 97%
See 1 more Smart Citation
“…Dose-response curves are shown in Figure 2 and the IC 50 values obtained from data fits are summarized in Table 1. Inhibition of glycerol permeability in hRBC by the same metal complexes [13,14] is also reported for comparison purposes. As shown in Figure 2, the cellular behavior under the influence of the phenanthroline compounds (Auphen and Cuphen) differs significantly from the bipyridine cores (p <0.001).…”
Section: Antiproliferative Effects Of Metal Compounds In Cancer Cellsmentioning
confidence: 97%
“…Moreover, the majority fails to undergo to clinical trials due to extreme toxicity. Recently, Martins et al described new gold-based coordination compounds as potent and selective inhibitors of the glycerol transport through AQP3 in human red blood cells (hRBC) [13,14]. Interestingly, all these gold complexes contain N-donor ligands and are also described as antiproliferative agents against cancer cells in vitro [15 -17] .…”
Section: Introductionmentioning
confidence: 99%
“…The inhibitor has also been used to impair membrane protrusion and bleb formation in AQP9 expressing cells [40]. The gold-based compound Auphen has been shown to elicit an inhibitory effect on AQP3 [41]. An inhibitor of AQP1 called AqB013 has shown promising effects on the migration and invasion of colon cancer cells in vitro [42].…”
Section: Aquaporinsmentioning
confidence: 99%
“…We demonstrated previously that the inhibition of cell proliferation was proportional to the reduction in glycerol permeability produced by Auphen. 18 Since the transport of glycerol by AQP3 is bidirectional, 59 proliferation could be related to the entry or exit of glycerol in cells; and unlike other authors, [60][61][62] we did not rule out the effect of Auphen on cell proliferation being caused by glycerol accumulation inside the cell due to blocking of the exit of glycerol. 18 AQP7 is the major pathway for glycerol efflux from adipocytes after lipolysis, 63,64 its absence resulting in increases in adipocyte cell volume and adipose tissue mass.…”
Section: Glycerolmentioning
confidence: 61%
“…20 A range of experimental approaches using drugs or specific culture conditions that allow manipulation of cell cycle progression have also contributed to our understanding of the role of AQPs in this process. For instance, we reported that cells with endogenous or exogenous, stable or transient, expression of AQP3 treated with Auphen, a potent inhibitor of the glycerol permeability of AQP3, 59 were arrested in the S-G2/M phases of the cell cycle, suggesting the possibility that the inhibition of AQP3 permeability somehow detains the progression of the cell cycle, thereby slowing cell proliferation. 18 In agreement with our results others have found that cell cycle of neurospheres derived from adult neuron stem cells of the subventricular zone (SVZ) in AQP4 knockout mice get arrested at the G2-M stage, 87 functionally implicating AQP4 in the activation and differentiation of the mice SVZ neurogenic niche.…”
Section: Cell Cycle and Aqpsmentioning
confidence: 99%